The presence of heparins during decidualization modulates the response of human endometrial stromal cells to IL-1β in vitro - Spratte, Julia; Schütz, Florian; Fluhr, Herbert (Journal of assisted reproduction and genetics, 2016)
The aim of this paper is to study the impact of heparin on the response of human endometrial stromal cells (ESCs) to interleukin (IL)-1β during decidualization in vitro.
Im Text wird beta als griechischer Buchstabe dargestellt
Gesehen am 12.05.2020